Exploring Research Trends in Science Education to be Implemented in the Elementary School - Syachruroji, Ahmad; Leksono, Suroso Mukti; Fathurrohman, Maman; Khastini, Rida Oktorida (Gemilang Maju Publikasi Ilmiah (GMPI), 2024)
Through an extensive bibliometric analysis, this study explored the ever-changing field of science education. In-depth analyses of publishing patterns, journal contributions, researcher output, institutional partnerships, and theme content and developmental paths in the field of scientific studies education are all included in the objectives. An exhaustive search of Scopus was used to gather research data from 2000 to 2023. Keywords including learning, science education, and elementary school were found in article titles, abstracts, and keywords. Research patterns were examined using Vos Viewer software, yielding important discoveries. The findings revealed that the highest number of research publications in the field of science education indexed in Scopus was observed in 2023, with 195 publications. Most international publications in this field were found in journal articles, with the United States being the leading contributor. The co-word analysis of the science education learning field identified eight clusters encompassing 88 themes associated with its development. These findings highlight the importance of interdisciplinary collaboration, focused investment in research areas, and the promotion of evidence-based approaches to improving educational outcomes in elementary schools. therefore, influence future research directions, policy formulation, and educational practices and advance knowledge in the field of science education.